Zentangle Art to Improving Mental Health: A Scoping Review - Hermanto, Edi; Kurnia, Galuh Mega; Nurmala, Ira; Devy, Shrimarti Rukmini (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Due to its increasing incidence, mental health has become a global concern in recent years. Therefore, academics, practitioners, and researchers have been searching for the best approach to mental well-being that will affect mental health. Art therapy has long been used as a tool to improve mental health. However, not all forms of art therapy are suitable for everyone. Zentangle, a method of drawing repetitive patterns, has attracted attention as one form of art therapy that is easy to learn and practice. Objectives: To explore the effectiveness of Zentangle in improving mental health. Methods: This review uses a Scoping Review using 3 databases: ProQuest, PubMed and ScienceDirect. The exclusion criteria are systematic review, scoping review and literature review. Of the 15 articles found, 6 were included in the inclusion criteria, which were then used as material for discussion in this article. Discussion: Findings from 6 articles show that Zentangle therapy can improve cognitive focus and emotional well-being, effectively alleviate Stress and lessen feelings of frustration, reduce symptoms of depression, foster compassion and encourage positive emotions. Conclusions: Zentangle therapy can foster positive emotions such as gratitude and self-achievement, improving physical, mental and spiritual well-being and thus positively affecting mental health.